Экология зернового точильщика — Rhizopertha dominica F. (Bostrychidae, Coleoptera) и его вредоносность в Таджикистане - Келимбетов, П.К. (Вестник зоологии, 1969)
Rhizopertha dominica was found for the first time in Tajikistan in 1955, it occurs lately in the whole territory of the Central, South-western and Northern Tajikistan. Two-three generations of Rhizopertha dominica can develop during a year in the Northern Tajikistan, and it propagates the whole year round in the South-western Tajikistan where the average daily winter temperature is not lower than 15°C. Rhizopertha dominica is a polyphagous pest — its larvae and beetles damage a great number of food-stuffs and forage and seeds of many cereals as well